(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The study examines the self-employment system based on theoretical and practical aspects of improving vulnerable employment, taking into account the characteristics of productive employment. At the same time, the types, structure and features of self-employment activities are considered, as well as national and international standards for its regulation, legal, organizational and economic opportunities for the effective use of the current mechanism, as well as features of international experience in improvement. the system has been studied. The article also discusses the development of the self-employment system in rural and urban areas, within the framework of which, to mitigate and eliminate factors that negatively affect the further increase in self-employment rates, reforms, measures and theoretical and scientific foundations aimed at increasing the income of the population through this type of employment.